THE USE OF RIDDLE GAME TO IMPROVE STUDENTS’ VOCABULARY - Yuliarsih Yuliarsih (The Ellite of Unira, 2022)
Vocabulary mastery is essential part of English as a foreign language. In teaching vocabulary, the teachers had responsibility to make their teaching successful. There are four ways of teaching vocabulary. Definitional methods, Contextual methods, Organizational and Mnemonic instructional methods. In this research the researcher used the contextual method. Riddle game is the nouns all refer to something baffling or confusing which is to be solved.  In this research the researcher used the qualitative research. After implementing riddle game, the criteria of success has been fulfilled. It means that the students’ vocabulary achievement was better than before. Based on these result, the students got many improvements, the improvements could be seen from the way they thought logically and creatively, they solved the puzzle the riddle provides and they did the test well.